Detection of filovirus-reactive antibodies in Australian bat species. (16th August 2022) - Barr, Jennifer; Boyd, Victoria; Todd, Shawn; Smith, Ina; Prada, Diana; O'Dea, Mark; Jackson, Bethany; Pearce, Lesley; Adams, Timothy E.; Vanderduys, Eric; Westcott, David; McKeown, Adam; et al.
Abstract : Bats have been implicated as the reservoir hosts of filoviruses in Africa, with serological evidence of filoviruses in various bat species identified in other countries. Here, serum samples from 190 bats, comprising 12 different species, collected in Australia were evaluated for filovirus antibodies. An in-house indirect microsphere assay to detect antibodies that cross-react with Ebola virus ( Zaire ebolavirus ; EBOV) nucleoprotein (NP) followed by an immunofluorescence assay (IFA) were used to confirm immunoreactivity to EBOV and Reston virus ( Reston ebolavirus ; RESTV). We found 27 of 102 Yinpterochiroptera and 19 of 88 Yangochiroptera samples were positive to EBOV NP in the microsphere assay. Further testing of these NP positive samples by IFA revealed nine bat sera that showed binding to ebolavirus-infected cells. This is the first report of filovirus-reactive antibodies detected in Australian bat species and suggests that novel filoviruses may be circulating in Australian bats.